Thermal Decomposition of Donor‐Stabilized Phosphinoborane PH2BH2NMe3: A Tensimetry Study. Issue 35 (16th September 2019) - Butlak, Alina V.; Kazakov, Igor V.; Stauber, Andreas; Hegen, Oliver; Scheer, Manfred; Pomogaeva, Anna V.; Timoshkin, Alexey Y.
Abstract: Invited for the cover of this issue are the groups of Alexey Y. Timoshkin from St. Petersburg State University, Russia, and Manfred Scheer from University of Regensburg, Germany. The cover image shows the thermal decomposition of Lewis base stabilized phosphanylborane under different conditions. Abstract : We try to understand the processes between synthetic molecular chemistry and polymer chemistry by vapor pressure measurements and quantum chemical computations … Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by A. Y. Timoshkin et al.